Faktor-Faktor Yang Mempengaruhi Terjadinya Stunting Pada Balita Di Desa Sumbul Tahun 2026 - Rianita Siagian; Rio Jenita Sipayung (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Stunting represents a state of chronic undernutrition occurring during the periods of growth and development from early life. Its occurrence can be attributed to various factors, including family and toddler characteristics, as well as inadequate nutrient intake coupled with infectious diseases in children. According to Mutia Nur (2026), 33 provinces recorded stunting prevalence rates among toddlers that exceeded the national average; among them, North Sumatra Province ranked 19th. Based on the Indonesian Nutritional Status Survey (SGGI), North Sumatra Province recorded a stunting prevalence of 21.1%. Kainjaihe is an area located in North Sumatra Province. Kainjaihe recorded a stunting prevalence rate of 16.16% in 2022; this figure is considered high, given the national target of reducing stunting prevalence to 14% by 2024 (Wahdini, 2024). This study aims to identify the factors contributing to stunting among toddlers.The study employed an analytical survey design with a cross-sectional approach. A total sampling technique was used, encompassing the entire population of 55 toddlers. Data analysis was conducted using the Chi-Square test.The results indicate that the factors associated with the incidence of stunting were maternal knowledge (α = 0.05, p = 0.001), parental education (α = 0.05, p = 0.002), and maternal diet during pregnancy (α = 0.05, p = 0.000).The study concludes that all the factors investigated are associated with the incidence of stunting among toddlers.